Integrating scholarly writing development into postgraduate research programmes: An exploration of enablers and constraints - Lamberti, P.; Kluyts, M.; de Klerk, D. (South African Journal of Higher Education, 2024)
In many South African universities, full research students receive little support during the research conceptualisation stage of the research journey, other than that provided by their supervisors, who tend to have limited time to engage with their students. Furthermore, during the proposal phase, scant attention is paid to the role of writing in research conceptualisation and scholarly development. In an attempt to address this neglect, the authors of this article worked collaboratively with academic staff from two schools within the Faculty of Commerce, Law, and Management at the University of the Witwatersrand to pilot academic literacies-informed projects aimed at integrating writing in the first year of existing postgraduate research programmes. This article provides insight into factors that constrain and enable such an integration endeavour. Data was collected through focus group discussions with the project teams from the participating schools. Drawing on Margaret Archer’s structure, culture, and agency as the analytical framework, five themes emerged from the data: leadership and oversight, supervision and postgraduate pedagogy, supervisor awareness and support, the postgraduate research education curriculum, and student engagement and commitment. The authors discuss these themes in terms of their enabling and constraining dimensions, and conclude with observations that could inform similar initiatives in other postgraduate research programmes.